Pragmatic clinical trials for localized prostate cancer: lessons learned and “three sins” - Roach, Mack (Frontiers in Oncology, 2024)
In “Explanatory and Pragmatic Attitudes in Therapeutic Trials”, Schwatrz and Lelouch describe two approaches to the design of trials, “… the first “explanatory”, the second “pragmatic”. They explained “… the biologist may be interested to know whether the drugs differ in their effects … the explanatory approach”. Biologically endpoints might determine whether it was better to give androgen deprivation therapy (ADT) before or after external beam radiation (EBRT) (i.e., does the sequence of treatments matter). Alternatively, if the arms focus on a clinical endpoint, this is considered … “the pragmatic approach”. An example of a clinically relevant endpoint is overall survival (OS). A real-world example of this are the two randomized controlled trials (RCTs) evaluating the role of prophylactic whole pelvic radiotherapy (WPRT) conducted by the Radiation Therapy Oncology Group (RTOG). RTOG 9413 evaluated possible interactions between the sequence of drugs and volume irradiated, while RTOG/NRG 0924 focuses on OS. There appears to be a common pattern of “what not to do”, or “design errors” made by a number of investigators, that I call the “three sins”. I posit that the prospects for a well-designed pragmatic RCT are likely to be high if these “three sins” are avoided/minimized. The “three sins” alluded to are: 1. You can’t prove something doesn’t work by treating people who don’t need the treatment. 2. You can’t prove something does not work if the treatment is not done properly. 3. You can’t prove something does not work with an underpowered study.